BPOM Supervision Negligence Review Results in Child Victims of Acute Kidney Failure - Harry Sunyoto; Amad Sudiro (Dinasti Research, 2025)
In 2022, the Indonesian Pediatrician Association (IDAI) through the Ministry of Health conveyed to the public that there were 324 cases of atypical progressive acute kidney failure of unknown cause in children spread across 27 provinces in Indonesia. The method used in this study is the normative research method by collecting secondary data which is then analyzed qualitatively to obtain conclusions about the circulation of syrup drugs that cause acute kidney failure in children, which is certainly not in accordance with the provisions in the Health Law and also violates the guidelines for Good Manufacturing Practices. The form of legal responsibility that can be carried out by BPOM is to strengthen the pre-market and post-market supervision function of drugs in circulation and conduct independent drug tests. In addition, it is hoped that the government will immediately ratify the Drug and Food Supervision Bill to strengthen the supervisory function, authority and sanctions that can be imposed on BPOM if they are negligent.